Dubious Actions Coming to Light: The Role of ‘Talking’ Gems as Indicators of Virtuousness - Florian Nieser (Memo, 2020)
This paper is dedicated to the speaking capabilities of gemstones, their mobility and their function of reminding us of elements hidden or repressed in the text. It will be shown that inscriptions made of gemstones shaped as words do not necessarily depend on the ‚arbitrariness‘ of their recipients. At the center is the wax tablet of Gregorius in Hartmann von Aue’s narrative, whose special material composition of partly perishable and partly durable materials is reassessed in comparative analysis of the epitaphs of fallen kings in Willehalm by Wolfram von Eschenbach and the Cupido-helmet from Wilhelm von Österreich by John of Wuerzburg. The focus in the contemplation of Gregorius‘ wax tablet changes from the weathered inscription on the tablet, which is no longer able to tell of the sinful past, to the weatherproof and gem-studded framing of this inscription, which materially stages the protagonist’s iridescent character biography. | Dieser Beitrag widmet sich der ‚Sprachfähigkeit‘ von Edelsteinen, ihrer Mobilität und ihrer erinnernden Funktion an im Text verheimlichte oder zurückgedrängte Elemente. Es soll gezeigt werden, dass Inschriften, die mittels zu Wörtern geformten Edelsteinen angefertigt wurden, nicht zwingend von der ‚Willkür‘ ihrer Rezipienten abhängen. Im Zentrum steht die Wachstafel des Gregorius in der Erzählung Hartmanns von Aue, deren besondere materielle Beschaffenheit aus teils vergänglichen und teils beständigen Materialien in vergleichender Analyse der Epitaphe gefallener Könige im Willehalm Wolframs von Eschenbach und dem Cupido-Helm aus dem Wilhelm von Österreich Johanns von Würzburg neu betrachtet wird. Der Fokus in der Betrachtung der Wachstafel des Gregorius wechselt von der verwitterten Inschrift auf der Tafel, die nicht mehr von der sündhaften Vergangenheit berichten kann, zur witterungsbeständigen und edelsteinbesetzten Rahmung dieser Inschrift, die die schillernde Figurenbiographie des Protagonisten materiell in Szene setzt.